Selection of Relevant Bacterial Strains for Novel Therapeutic Testing: a Guidance Document for Priority Cystic Fibrosis Lung Pathogens - Eshwar Mahenthiralingam; Rebecca Weiser; R. Andres Floto; Jane C. Davies; Joanne L. Fothergill (Current Clinical Microbiology Reports, 2022)
Purpose of Review People with cystic fibrosis (CF) suffer chronic lung infections with a range of antimicrobial-resistant bacterial pathogens. There is an urgent need for researchers to develop novel anti-infectives to treat these problematic infections, but how can we select bacterial strains which are relevant for robust testing and comparative research? Recent Findings Pseudomonas aeruginosa , Burkholderia cepacia complex and Burkholderia gladioli , Mycobacterium abscessus complex, Staphylococcus aureus, Haemophilus influenza, and several multidrug-resistant Gram-negative species were selected as key CF infections that urgently require new therapeutics. Reference isolates and strain panels were identified, and a summary of the known genotypic diversity of each pathogen was provided. Summary Here, we summarise the current strain resources available for priority CF bacterial pathogens and highlight systematic selection criteria that researchers can use to select strains for use in therapeutic testing.